GAMBARAN KARAKTERISTIK PASIEN KRITIS DI AREA CRITICAL UNIT - Albertus Budi Arianto; Elsya Fernita Rosanti; Linda Sari Barus (Jurnal Kesehatan, 2022)
Description of characteristics of critical patients in area critical unit. The entry characteristics of intensive care units are necessary for the development of critical care services. The criteria of patients who are in intensive care are critical patients with instability or organ system failure that require intensive management. The purpose of this study is to determine the characteristics of critical patients in the critical unit. Method used in this research is quantitative with descriptive design that uses secondary data. The data was obtained from the medical records of HCU-ICU state hospitals in West Bandung Regency with 167 samples. Results of the study showed that the majority of critical patients are female (63.5%), aged 56 - 65 years (28.1%), cardiac disease comorbidity (19.8%), emergency installation room origin (IGD) (55.7%), primary diagnosis of neurological disorders (25.7%), using monitors during HCU-ICU (97%), using antibiotics while in HCU-ICU (50.3%), length of treatment > 7 days (88%), and prognosis of patients cured or moved to the infirmary (75.4%). The results of this study of gender and age characteristics with comorbid and primary diagnoses obtained by critical patients showed most middle-aged women aged 56-65 years comorbid heart disease with neurological disorders so more research is needed on other characteristics to provide a more comprehensive understanding.